Are you following a man?: Lived experiences of women in the workplace - Cheryl Kennedy; Katherine Chapman (Adult Education Research Conference, 2024)
This study provides human resource professionals insight into how women experience the workplace. The authors applied relational ethnography to explore the effect of patriarchy on women in higher education.
Keywords: Emotional Labor; Patriarchy; Relational Ethnography; Women’s Developmental Theory